Sonographical parameters of the finger pulley system in healthy adults - Bassemir, Dominik; Unglaub, Frank; Hahn, Peter; Müller, Lars Peter; Bruckner, Thomas; Spies, Christian (Archives of orthopaedic and trauma surgery, 2015)
Introduction To establish normative values of tendon to bone distances (TBDs) to evaluate the A2 and A4 annular pulley integrity, we hypothesized that these values correlate with gender, athletic exercise, occupation, individual’s age and body height.Methods Ultrasonography of 200 healthy individuals was performed prospectively. TBDs for the A2 and A4 pulley sections were measured for all fingers. Evaluation was performed in resting position and active forced flexion. Examination parameters included gender, age, body height, occupation, athletic exercise level, and hand dominance. Assessment of resting position and active forced flexion was done.ResultsNo clinically relevant differences of TBDs with respect to the aforementioned parameters were observed. But TBDs were significantly greater in active forced flexion than in resting position for all measured pulley sections. Intraobserver reliability was very satisfactory.ConclusionsEstablishing normative values will help to detect injured pulleys more precisely and examination should be performed both in resting position and active forced flexion.
Gesehen am 14.12.2017